2014
DOI: 10.1016/j.ijgo.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of dilation and curettage/evacuation by manual vacuum aspiration and medical abortion, and the introduction of postabortion contraception in Pakistan

Abstract: Manual vacuum aspiration (MVA) and medical abortion were introduced to replace dilation and curettage/evacuation for incomplete abortions, and postabortion contraception was provided in 5 selected public hospitals in Pakistan. In the largest hospital, an Ipas MVA training center since 2007, MVA use reached 21% in 2008. After the International Federation of Gynecology and Obstetrics (FIGO) and UNFPA provided MVA kits, MVA use increased dramatically to 70%-90% in 2010-2013. In 2 of the remaining 4 hospitals in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Graff and Amoyaw (2009) found that a lack of prioritizaiton of PAC in Ghana led to purchasing equipment for other services rather than MVA when funds were limited. Moreover, purchasers may not appreciate MVA's advantages as equipment is more expensive and does not last as long as curettage equipment (Zaidi et al 2014), although it is still more cost-effective as it can be performed as an outpatient procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Graff and Amoyaw (2009) found that a lack of prioritizaiton of PAC in Ghana led to purchasing equipment for other services rather than MVA when funds were limited. Moreover, purchasers may not appreciate MVA's advantages as equipment is more expensive and does not last as long as curettage equipment (Zaidi et al 2014), although it is still more cost-effective as it can be performed as an outpatient procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, misoprostol has been used for hospital-based induction of labour and uterine evacuation since the 1990s 14. It was not, however, until 2012, after misoprostol was put on the 16th World Health Organization Model List of Essential Medicines, that Pakistan permitted its availability in the country for prevention and treatment of postpartum haemorrhage and management of incomplete abortion 14.…”
Section: Introductionmentioning
confidence: 99%
“…It was not, however, until 2012, after misoprostol was put on the 16th World Health Organization Model List of Essential Medicines, that Pakistan permitted its availability in the country for prevention and treatment of postpartum haemorrhage and management of incomplete abortion 14. In 2014, clinical protocols for use of the drug were endorsed by all provincial health departments and the drug's use was included in Pakistan's nursing, community midwifery and community health worker training curriculum 3 7 15…”
Section: Introductionmentioning
confidence: 99%
“…Mayi and Zaidi had the same attitude, giving priority to contraceptives with long duration action in their practice on the PAC on patients with low sociodemographic status. 9,13 Finally, the screening of cervical cancer was freely performed in all patients (176 patients or 78.57%) who fulfilled their 6 weeks consultation. It allowed us to screen 5 positive results; all of them were low grade lesions (2.92%).…”
Section: Pacmentioning
confidence: 99%